2021
DOI: 10.1002/slct.202100978
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Chemo‐ and Regioselectivity of the [3+2] Cycloaddition Reaction between 4‐Chlorobenzonitrile Oxide and β‐Aminocinnamonitrile with a MEDT Perspective**

Abstract: A molecular electron density theory (MEDT) study for the [3 + 2] cycloaddition (32CA) reaction of 4-chlorobenzonitrile oxide (CBNO) and β-aminocinnamonitrile (ACN) has been performed at the MPWB1K/6-311G(d,p) computational level. This 32CA reaction, characterised as the zwitterionic type (zw-type), presents an activation enthalpy of 11.8, 14.2 and 16.6 kcal mol À 1 , in gas phase, benzene and methanol. The formation of 3-aryl-5-(β-aminostyryl)-1,2,4-oxadiazole is predicted as the energetically feasible one fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…The most relevant finding from this BET study is that despite the Parr functions accounting for the solely isolation of regioisomeric isoxazolines 3b,e, formation of the C3-C5 single bond involving the least nucleophilic and electrophilic centers of the reagents takes place before the expected more favorable O1-C5 one. This unexpected pattern is also observed in previous BET studies of polar zw-type 32CA reactions of NOs [57,63]. On the other hand, the similar bonding changes taking place along the 32CA reactions of the two most electronically different NOs 1b and 1e with TNP 2 indicates that the computed reactivity changes among the series of NOs 1a-e are mainly due to their different nucleophilic character and polarity of the corresponding reactions, rather than any structural or mechanistic reason.…”
Section: Characterization Of the Bond Formation Processsupporting
confidence: 83%
See 1 more Smart Citation
“…The most relevant finding from this BET study is that despite the Parr functions accounting for the solely isolation of regioisomeric isoxazolines 3b,e, formation of the C3-C5 single bond involving the least nucleophilic and electrophilic centers of the reagents takes place before the expected more favorable O1-C5 one. This unexpected pattern is also observed in previous BET studies of polar zw-type 32CA reactions of NOs [57,63]. On the other hand, the similar bonding changes taking place along the 32CA reactions of the two most electronically different NOs 1b and 1e with TNP 2 indicates that the computed reactivity changes among the series of NOs 1a-e are mainly due to their different nucleophilic character and polarity of the corresponding reactions, rather than any structural or mechanistic reason.…”
Section: Characterization Of the Bond Formation Processsupporting
confidence: 83%
“…In polar reactions, the formation of the first single bond takes place between the most nucleophilic center of the nucleophile and the most electrophilic center of the electrophile as characterized by CDFT and the Parr functions. Accordingly, in zw-type 32CA reactions of NOs, this should be the C-O single bond (see Section 2.2.2); however, previous BET studies [57,63] have shown that regardless of the polar character, the C-C single bond forms first in 32CA reactions of NOs.…”
Section: Characterization Of the Bond Formation Processmentioning
confidence: 99%
“…The GEDT values of TS1 and TS2 are 0.07 e and 0.05 e, while those at TS3 and TS4 are between 0.08 e and 0.07 e. The slight increase in GEDT of the TSs associated with the IM32CA reaction of 18 relative to that of 15 can be attributed to the higher electronic chemical potential m of 31 (m = À2.56 eV), the alkene fragment of 18, relative to that of 30 (m = À3.01 eV), and the alkene fragment of 15 (Table 2). Note that the GEDT values at TS5-TS8 are between 0.03 and 0.05 e, suggesting minimal electronic flux, consistent with the minimal difference in the electronic chemical potentials and the marginal electrophilicities of the nitrone (29) and alkene (32)(33)(34) moieties, predicting the nonpolar character.…”
Section: Analysis Of the Cdft Indicessupporting
confidence: 54%
“…The pdr-type [3] and pmr-type [4] 32CA reactions could be related with the Firestone's mechanism, [8] although the pseudoradical centers of TACs do not correspond to the formation of actual radical centers, but to the presence of non-bonding electron density at one carbon center integrating less than 1 e. [3] On the other hand, the cbtype [6] 32CA reactions involving carbenoid centers characterized by the presence of non-bonding electron density at a carbon integrating almost 2 e, cannot be related to the electronic structures proposed by Huisgen [7] and Firestone [8] for the TACs. MEDT has been recently applied to study the correlation between changes in electron density and the molecular reactivity to analyze various aspects of 32CA reactions, namely the strain promotion, [14,15] substituent effects, [16,17] chemo-, [18,19] regio [5] -and stereoselectivity, [5,20] catalysis, [21,22] etc.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the cb‐type [6] 32CA reactions involving carbenoid centers characterized by the presence of non‐bonding electron density at a carbon integrating almost 2 e, cannot be related to the electronic structures proposed by Huisgen [7] and Firestone [8] for the TACs. MEDT has been recently applied to study the correlation between changes in electron density and the molecular reactivity to analyze various aspects of 32CA reactions, namely the strain promotion, [14,15] substituent effects, [16,17] chemo‐, [18,19] regio [5] ‐ and stereoselectivity, [5,20] catalysis, [21,22] etc.…”
Section: Introductionmentioning
confidence: 99%